Bridging Instructional Gaps through Recognizing the Factors and Students’ Experiences in Distance Learning (International Journal of Theory and Application in Elementary and Secondary School Education, 2022)
This study assesses the factors affecting students' learning experiences in one of the secondary public schools in the Philippines implementing different learning modalities in distance learning. As a learner-public institution, the school has broadened its implementation of learning by providing wide perspectives to students through online distance learning. The study utilized quantitative and qualitative research designs. Purposive sampling was used in the study consisting of 250 students and 18 students who participated in FGD, where data were collected and obtained through a survey questionnaire and focus group discussions. Distance learning encourages students to learn on their own and explore without the assistance of teachers, enhancing their ability to research topics related to the courses they should learn. With the results of the study, two themes emerged: ICT integration and innovational instruction. Mostly, it aided in the development of independence. Students usually lose concentration in their learning tasks as a result of physical distractions and due to slow internet connection. Regardless of their difficulties, students continue their studies because they have learned that the more difficult the road, the sweeter the result. This study will provide baseline information for the development of the school's strategy on how to strengthen and consolidate distance education.